Explaining Intergovernmental Conflict in the COVID-19 Crisis: The United States, Canada, and Australia. Issue 4 (15th June 2021) - Lecours, André; Béland, Daniel; Fenna, Alan; Fenwick, Tracy Beck; Paquet, Mireille; Rocco, Philip; Waddan, Alex
Abstract: The Covid-19 pandemic produced more significant immediate intergovernmental conflict in the U.S. than in Australia and Canada. This article considers three variables for this cross-national divergence: presidentialism versus parliamentarism; vertical party integration; and strength of intergovernmental arrangements. We find that the U.S. presidential system, contrary to parliamentarism in Canada and Australia, provided an opportunity for a populist outsider skeptical of experts to win the presidency and pursue a personalized style that favored intergovernmental conflict in times of crisis. Then, the intergovernmental conflict-inducing effect of the Trump presidency during the pandemic was compounded by the vertical integration of political parties, which provided incentives for the President to criticize Democratic governors and vice-versa. Third, the virtual absence of any structure for intergovernmental relations in the United States meant that, unlike Australian states and Canadian provinces, American states struggled to get the federal government's attention and publicly deplored its lack of leadership.